Treatment with vitamin D/MOG association suppresses experimental autoimmune encephalomyelitis - Chiuso-Minicucci, Fernanda [UNESP]; Watanabe Ishikawa, Larissa Lumi [UNESP]; Nishiyama Mimura, Luiza Ayumi [UNESP]; Campos Fraga-Silva, Thais Fernanda de [UNESP]; Donega Franca, Thais Graziela [UNESP]; Fernanda Goncalves Zorzella-Pezavento, Sofia [UNESP]; Marques, Camila; Valerio Ikoma, Maura Rosane; Sartori, Alexandrina [UNESP] (Public Library Science, 2015)
Experimental autoimmune encephalomyelitis (EAE) is an animal model to study multiple sclerosis (MS). Considering the tolerogenic effects of active vitamin D, we evaluated the therapeutic effect of myelin oligodendrocyte glycoprotein (MOG) associated with active vitamin D in EAE development. EAE was induced in female C57BL/6 mice by immunization with MOG emulsified with Complete Freund's Adjuvant plus Mycobacterium tuberculosis. Animals also received two intraperitoneal doses of Bordetella pertussis toxin. One day after immunization, mice were treated with 0,1 mu g of 1 alpha,25-dihydroxyvitamin D3 (1,25(OH)(2)D-3) every other day during 15 days (on days 1, 3, 5, 7, 9, 11, 13 and 15). MOG (150 mu g) was coadministered on days 3 and 11. The administration of 1,25(OH)(2)D-3 or MOG determined significant reduction in EAE incidence and in clinical scores. When MOG was associated with 1,25(OH)(2)D-3 the animals did not develop EAE. Spleen and central nervous system (CNS) cell cultures from this group produced less IL-6 and IL-17 upon stimulation with MOG in comparison to the EAE control group. In addition, this treatment inhibited dendritic cells maturation in the spleen and reduced inflammatory infiltration in the CNS. The association of MOG with 1,25(OH)(2)D-3 was able to control EAE development.